Unveiling the gut microbiota and metabolite profiles in guinea pigs with form deprivation myopia through 16S rRNA gene sequencing and untargeted metabolomics - Yajun Wu; Hua Fan; Yuliang Feng; Jiasong Yang; Xiaobo Cen; Wensheng Li (Heliyon, 2024)
Aim: The aim of this study was to confirm the presence of the form deprivation myopia (FDM) guinea pig eye-gut axis and investigate the relationship between serum vasoactive intestinal peptide (VIP), lipopolysaccharides (LPS), specific gut microbiota and their metabolites. Method: 20 specific-pathogen-free (SPF) guinea pigs were divided into the FDM and the control(Con) group. Following model induction, serum levels of VIP and LPS were quantified. A combination of 16S ribosomal ribosomal Ribonucleic Acid (rRNA) gene sequencing, non-targeted metabolomics and bioinformatics analysis were employed to identify disparities in gut microbiota and metabolites between the two groups of guinea pigs. Result: Compared to the control group, FDM guinea pigs exhibited a significant trend towards myopia, along with significantly elevated concentrations of LPS and VIP (p < 0.0001). Furthermore, Ruminococcus_albus emerged as the predominant bacterial community enriched in FDM (p < 0.05), and demonstrated positive correlations with 10 metabolites, including l-Glutamic acid, Additionally, Ruminococcus_albus exhibited positive correlations with VIP and LPS levels (p < 0.05). Conclusion: The findings suggest that the Ruminococcus_Albus and glutamate metabolic pathways play a significant role in myopia development, leading to concurrent alterations in serum VIP and LPS levels in FDM guinea pigs. This underscores the potential of specific gut microbiota and their metabolites as pivotal biomarkers involved in the pathogenesis of myopia.